Particle Size Analysis in Aerosol-Generating Dental Procedures Using Laser Diffraction Technique - Onoyama, Kaoru; Matsui, Shohei; Kikuchi, Mariko; Sato, Daisuke; Fukamachi, Haruka; Kadena, Miki; Funatsu, Takahiro; Maruoka, Yasubumi; Baba, Kazuyoshi; Maki, Kotaro; Kuwata, Hirotaka (Frontiers in Oral Health, 2022)
The global outbreak of coronavirus disease 2019 (COVID-19) has raised concerns about the risk of airborne infection during dental treatment. Aerosol-generating dental procedures (AGDP) produce droplets and aerosols, but the details of the risks of COVID-19 transmission in AGDP are not well understood. By discriminating between droplets and aerosols, we devised a method to measure particle size using laser diffraction analysis and evaluated aerosols generated from dental devices for providing a basis for proper infection control procedures. The droplets and aerosols generated from dental devices were characterized by multimodal properties and a wide range of droplet sizes, with the majority of droplets larger than 50 µm. AGDP emitted few aerosols smaller than 5 µm, which are of concern for pulmonary infections due to airborne transmission. In addition, the use of extraoral suction was found to prevent the spread of aerosols from high-speed dental engines. This study suggests that the risk of aerosol infections is considerably limited in regular dental practice and that current standard precautions, such as mainly focusing on protection against droplet and contact infections, are sufficient. While several cases of airborne transmission of COVID-19 in general clinics and emergency hospitals have been reported, cluster outbreaks in dental clinics have not yet been reported, which may indicate that AGDP does not pose a significant threat in contributing to the spread of SARS-CoV-2.